The association between laboratory risk indicator for necrotizing fasciitis score with clinical signs and symptoms of necrotizing fasciitis: a retrospective study - Chauhan, Ajay; Patel, Yashashvi; Chauhan, Amit S.; Mehta, Fateh S. (International Surgery Journal, 2021)
Background: The term necrotizing soft tissue infection encompassing simple pyoderma to life threatening infection, varying with regards to anatomical location, tissue involvement and offending organism. Early diagnosis of necrotizing-STI is important for timely surgical intervention, but physical findings can vary, so misdiagnosis is common. By using WBC, CRP, haemoglobin, Na, creatinine, glucose and clinical examination we can distinguish NF from other STI. Methods: This was a retrospective and randomized study in the Geetanjali Medical College and Hospital affiliated to Geetanjali University from January 2017 to January 2019 during this period total 66 patients with soft tissue Infection were admitted and included. Clinical details and investigations were recorded from the case sheet and were analyzed with WBC, CRP, Hb, Na, creatinine and glucose. Results: The most commonly affected age group was 46-60 years with male preponderance. Most common cause of STI was Trauma 66.66% of the patients having Primary Site Lower Limb in 12.12% and as per LRINEC score 50% of the patients have low risk, 37.87% of the patients have high risk and strongly in favour of NF and 12.12% of the patients have intermediate risk. Conclusions: The LRINEC score is a good tool for NF risk stratification and patients are advised to be careful for presence of NF if LRINEC score is≥6.